Un Américain au Louvre ? L’architecte William Welles Bosworth et le réaménagement du musée du Louvre dans le cadre du « plan Verne » (1925-1939) - Églantine Pasquier (Les Cahiers de l'École du Louvre)
As soon as he became head of the Musées nationaux in 1925, Henri Verne began to put in place a vast project to reorganise and modernise the Louvre, known as the “plan Verne”. In search of 50 million francs of financing, he contacted William Welles Bosworth, the architect who represented John D. Rockefeller Jr. in France, so that he could help him find an American sponsor. While Rockefeller Jr. envisaged taking the project on for a time, in the end he decided to leave the responsibility to the French government. However, it is likely that Bosworth, owing to his experience as an architect and his knowledge of American museums, remained informally associated with the “plan Verne” as an adviser. The various leads supporting this hypothesis will be presented with a view to throwing new light on an eventual American contribution to reorganisation of the Louvre during the interwar period.